Kiwigaster gen. nov. (Hymenoptera: Braconidae) from New Zealand: the first Microgastrinae with sexual dimorphism in number of antennal segments - Fernandez-Triana, J. L.; Ward, D. F.; Whitfield, J. B. (Zootaxa, 2011)
A new and morphologically unusual genus of microgastrine Braconidae, Kiwigaster Fernandez-Triana, Whitfield and Ward, with one new species, K. variabilis Fernandez-Triana and Ward, is described from New Zealand, where it is widespread. A number of morphological features mark it as unique among Microgastrinae, the most striking being the males and females having different numbers of antennal flagellomeres (females 17, males 18). Other unusual characters suggest this may be the most early-diverging extant species of the subfamily, although comprehensive phylogenetic analyses have yet to be conducted. Nothing is yet known about its host(s) or other aspects of its biology.